Adaptive Control Design for Aeroelastic Suppression of Wind Turbine Blade. Issue 2 (April 2013) - Li, N.; Balas, M.J.
An aeroelastic model is introduced to analyze blade dynamics and design control strategy of blade vibration suppression. The model is a typical pitch and plunge system coupled with Beddoes-Leishman dynamic stall model, which describes unsteady flow over the spinning blade. The nonlinear B-L model is linearized for control design and stability analysis purpose. And the linearization is also validated by comparison of linear B-L model with nonlinear one, showing good agreement. The robustness and effectiveness of Adaptive Controller are shown by simulation tests with a wide range of aerodynamic loads, to guarantee the efficiency of wind power generation. In addition, stability of the controller is proven by the given Adaptive Stability Theorem, which is also demonstrated numerically by certain cases.